PENGARUH SIKAP INOVATIF DAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH, TERHADAP KREATIVITAS GURU DI SMK - Suharlan Suharlan; Aliman Aliman; Puspa Djuwita (Manajer Pendididikan, 2017)
The problem of this research to know inovative atitude and transformational leadership style to creative teacher Senior high vocational school one Ketahun 42 teachers.Sample taken by tecnic correlation counted 42 sampel. This research is analysed with descriptive statistic technique and inferensial to know the direct influence and indirect influence between variabel tested with band analysis. Result of the research  show: (1) They are positive direct  of inovative atitude and to creative teacher (2) They are direct positive influence between transformational leadership trough the teacher creativity of senior high school vokasional one Ketahun (3 They are direct positive between inovative atitude and transformational as together toward the teacher of Senior high school  vocational one Ketahun teachers.